Development of a workflow for the detection of vancomycin-resistant Enterococcus faecium and Enterococcus faecalis from rectal swabs using the spectra VRE medium - Kendall Kling; Javier Rios; Laura Dirnberger; Wanda Polanco; Kevin Fritz; Michael Malczynski; Teresa Zembower; Chao Qi (BMC, 2023)
Abstract Background Spectra™ VRE agar (Remel, Lenexa, KS) is a chromogenic agar that is FDA approved for screening patients for VRE colonization. The package insert recommends confirming isolates with identification and susceptibility testing, but confirming every culture delays time to result. Given the agar's historic high specificity for E. faecium isolates, we theorized the agar could be utilized as a stand-alone screening to minimize reagents and time. Aim Our laboratory sought to develop a workflow to optimize the use of the medium. Methods We plated 3,815 rectal swabs to the Spectra VRE agar and compared results to traditional identification and susceptibility testing. Results Dark blue or purple colonies on the agar demonstrated a sensitivity of 98% and specificity of 85% for detection of VRE faecium, but light blue colonies were significantly less specific for E. faecalis. Conclusions We streamlined our workflow to accept dark blue or purple colonies as VRE faecium and plan to perform additional testing only on light blue colonies. Interestingly, higher quantity of growth increased the accuracy of the agar. In the future, growth quantity may be used to further streamline the workflow once more data is obtained.